Sociodemographic Determinants of Willingness and Extent to Pay for COVID-19 Vaccine in India - Kiran, Tanvi; Junaid, K. P.; Sharma, Divya; Jain, Lovely; Vij, Jatina; Satapathy, Prakasini; Chakrapani, Venkatesan; Patro, Binod Kumar; Kar, Sitanshu Sekhar; Singh, Ritesh; Pala, Star; Bali, Surya; et al. (Frontiers in Public Health, 2022)
Background Responding to the fast transmission rates and increasing fatality rates, countries across the world expedited the development and deployment of the vaccine for coronavirus disease 2019 (COVID-19). Evaluation of individuals' willingness to pay (WTP) would provide pertinent information regarding future demand and financing preferences, which shall help to devise the effective payment strategy for COVID-19 vaccination. Methods A nationwide, cross-sectional, and self-administered online survey using a structured questionnaire was conducted to identify the sociodemographic determinants of willingness and extent to pay for COVID-19 vaccine in India. A non-probability convenience sampling followed by snowball sampling was employed to recruit participants (n = 3,341). The likelihood of sociodemographic determinants to predict willingness and extent to pay was modeled using the multivariate binary logistic regression analysis. Results Out of 3,341 participants, 68% (n = 2,271) were willingness to pay for COVID-19 vaccine. Results showed significantly higher odds for willingness to pay among participants who were single [adjusted odds ratio (aOR) = 1.394, p < 0.01] and having a family size of 4 members (aOR = 1.346, p < 0.01). The adjusted odds ratio sizably increased from 1.396 for participants whose monthly income was between INR 10,000 and 20,000/month to 2.240 for participants whose monthly income was above INR 50,000/month. Further, out of 2,271 of those participants who were willingness to pay for COVID-19 vaccine, majority (n = 1,246, 54.9%) of participants were willingness to pay below 50% of COVID-19 vaccine cost. This study found that those who are single (aOR = 0.688, p < 0.01), having an income between INR 20,000 and 50,000/month (aOR = 0.686, p < 0.05), and those who belonged to socially disadvantaged category (aOR = 0.450, p < 0.01) were estimated to have significantly lower odds of willingness to pay more than 50% of COVID-19 vaccine cost. Conclusion This study observed that majority of those participants who willingness to pay for COVID-19 vaccine were willingness to pay only up to 50% of COVID-19 vaccine and income was observed as a precursor predictor of the willingness and extent to pay for COVID-19 vaccine. The understanding on the willingness and extent to pay for COVID-19 vaccine and its sociodemographic determinants will be helpful for making the strategic decisions related to the financing of COVID vaccine in India.